BARKODING DNA BURUNG ELANG (FAMILI ACCIPITRIDAE) DI INDONESIA - Zein, Moch Syamsul Arifin (Research Center for Biology-Indonesian Institute of Sciences, 2018)
The cytochrome c oxidase subunit I (COI) gene is a reprensentative of all the protein-coding genes of the mitochondrial DNA genome that has been widely used as an animal species identification tool. In this study, 86 sequences of DNA barcodes of members of the family Accipitridae in Indonesia including Nisaetus bartelsi, Nisaetus cirrhatus, Haliaeetus leucogaster, Spilornis cheela, Haliastur indus, and 11 sequences from Genbank were examined. Each species was confirmed through the Basic Local Alignment Search Tool (BLAST). The construction of phylogeny trees based on COI gene sequences was performed by the Neighbors-joining method where the calculation of the genetic distance matrix with the Kimura 2-parameter model was implemented in pairwise distance calculation in the Mega version 6.05 programe. The results of the analysis showed that the divergence within species ranged from 0 to 0.3% (0.13 Â± 0.12%), between species ranged from 1.6 to 18.5% (12.8 Â± 3.73%), between genera ranged from 13 to 18.6%, and the average in the Accipitridae Family was 11.8%. Therefore, it could form clusters in each species cohesively and clearly separated between the taxa analyzed.